Lab work activities of computer network using virtual reality application - Sukirman, Sukirman; Sanjaya, Achmad Midun; Selfi, Reni (Telkomnika, 2021)
Lab work activities are one of the hearts of science learning, but several students have limited use and time to explore computer network tools. This study proposes a virtual reality (VR) application used to support lab work activities of a computer network so that students may conduct lab work activities by themselves at any time. The method used in this study is a multimedia development life cycle (MDLC) that consists of five stages, they are concept, design, material collecting, assembly, and testing & evaluation. A formative evaluation carried out by involving two experts, namely software expert and material expert, to measure the feasibility of application before conducting user testing. Meanwhile, a summative evaluation used to evaluate the VR application by involving 25 students who were taking the course of computer networking. Statistical analysis shows that the score of Cronbach's alpha test is higher than 0.6 for aspects of material subject and experience. Hence, the VR application can be used to support the lab work activities of a computer network.